Repetitive source of pulsed electron beams; Известия вузов. Физика; Т. 55, № 10-3 - Egorov I. S. Ivan Sergeevich; Remnev G. E. Gennady Efimovich; Kaikanov M. I. Marat Islambekovich; Lukonin E. I. Evgeny Ivanovich; Esipov V. S.; Poloskov A. V. Artem Viktorovich; Kolokolov D. Yu. Dmitry Yurievich (2012, 2012)
Заглавие с экрана